Culture and finance in a globalised world – An uneasy relation - Beate Reszat (Hamburg Institute of International Economics (HWWA), 2000)
At the turn of the century, the role of culture in society is changing. One facet of this change is the relation between culture and finance. Globalisation has led to an increasing competition between financial centres worldwide and culture has become one determinant of competitiveness. But, culture is also adapting to finance in that it responds to the requirements of globalisation and to the needs and desires of a place's financial community. The paper analyses these two sides of interaction between finance and culture emphasising the role of collective memory and cultural identity for the representation of financial centers and taking a closer look at the role of the arts among the variety of forms of cultural practices. Then the attention is drawn to two recent phenomena which, at first sight, seem to reduce the future importance of financial places and thereby also perhaps their influence on the culture world: The ever-increasing proportion of financial decisions made in so-called 'non-places' and the role of finance in a virtual world. – – Zu Beginn des neuen Jahrtausends ist die Rolle der Kultur in der Gesellschaft einem tiefgreifenden Wandel unterworfen. Ein Aspekt dieses Prozesses ist das Verhältnis von Kultur- zu Finanzwelt. Globalisierung hat dazu geführt, daß die Finanzzentren der Welt in immer stärkerem Wettbewerb zueinander stehen, und Kultur ist ein bestimmendes Element der Wettbewerbsfähigkeit eines Finanzplatzes. Aber Kultur paßt sich auch an die Finanzwelt an, in dem sie auf die Erfordernisse, die die Globalisierung mit sich bringt, und die Bedürfnisse der "financial community" reagiert. Die folgende Anlayse befaßt sich mit der Interaktion von Kultur- und Finanzwelt, wobei ein besonderes Augenmerk auf die Rolle der Kunst für die Repräsentation von Finanzzentren gerichtet ist. Zudem untersucht sie zwei Phänomene, die auf den ersten Blick die zukünftige Bedeutung von Finanzplätzen und dementsprechend auch den Einfluß der Finanzwelt auf die Kulturwelt schmälern: die Zunahme von Finanzentscheidungen, die an sogenannten "Nicht-Orten" getroffen werden, und die Rolle virtueller Finanzaktivitäten.
Keywords: R51; Z1; F3; 330; International Finance; Finance in Urban Economies; Cultural Economics; Finanzsektor; Kultursektor; Finanzplatz; Kunst; Kulturökonomik; Globalisierung; Welt